Climacteric and menopause: guidelines from the pharmacist and the impact on women's health (Research, Society and Development, 2021)
This study aims to present women in menopause, analyzing their priority care and guiding them to have adequate monitoring in health promotion. The woman's life is marked by the menarche phase, pregnancy and the last menstrual period, requiring an extraordinary care with this change. After analysis and interpretation of the selected studies, questions emerged that should be answered during the referential: "The role of the pharmacist in the care of women in climacteric and menopause", "What is the role of the pharmacist in the care of women from the impacts caused by climacteric and menopause?" and "Pharmaceutical guidance on the use of menopausal medications and incompatible interaction in pharmacotherapy. Objective: is to present the difficulties of women in this phase, sexuality, symptomatology and health education. Material and Methods: presented in the form of bibliographic reference, which were searched in more current articles, publications that address the woman in menopause and climacteric. Results: It was observed that in this menopausal period there are psychological, physical and social interferences. Conclusion: Given the research done, it was understood how important it is that health professionals are qualified so that they can provide attention to this menopausal woman and seek knowledge so that they can help these women doing actions for their quality of life to improve before these difficulties that is obtained in the transition to menopause remembering that health in the periphery is scarce, that is the woman in this period requires an attention focused on this cause.